Multiple Products and Oligopoly Strategy: A Development of Chamberlin's Theory of Products - Lanzillotti, Robert F. (Quarterly Journal of Economics, 1954)
Introduction, 461. — I. The traditional approach to oligopoly market strategy, 462. — II. Competition via self-competing products, 465. — III. Product diversification across industry lines, 460. — IV. Other considerations — summary, 472.